A decade of mangrove conservation achievements and challenges in Vietnam - Pham Thu Thuy; Nguyen, V.D. (Center for International Forestry Research, 2021)
The last decade has seen significant and marked improvements in the legal framework on mangrove protection, increased funding and involvement of non-state actors in mangrove protection and development, lower rates of mangrove forest loss and larger areas of planted mangroves in Vietnam. Despite these remarkable achievements, challenges remain for mangrove conservation, particularly when major drivers of mangrove deforestation and degradation have yet to be properly addressed as they are closely linked to national economic development priorities.